Hox11 Function is Required for Region-Specific Fracture Repair - Rux, Danielle R. (J Bone Miner Res, 2017)
The processes that govern fracture repair rely on many mechanisms that recapitulate embryonic skeletal development. Hox genes are transcription factors that perform critical patterning functions in regional domains along the axial and limb skeleton during development. Much less is known about roles for these genes in the adult skeleton. We recently reported that Hox11 genes, which function in zeugopod development (radius/ulna and tibia/fibula), are also expressed in the adult zeugopod skeleton exclusively in PDGFRα+/CD51+/LepR+ mesenchymal stem/stromal cells (MSCs). In this study, we use a Hoxa11eGFP reporter allele and loss-of-function Hox11 alleles, and we show that Hox11 expression expands after zeugopod fracture injury, and that loss of Hox11 function results in defects in endochondral ossification and in the bone remodeling phase of repair. In Hox11 compound mutant fractures, early chondrocytes are specified but show defects in differentiation, leading to an overall deficit in the cartilage production. In the later stages of the repair process, the hard callus remains incompletely remodeled in mutants due, at least in part, to abnormal bone matrix organization. Overall, our data supports multiple roles for Hox11 genes following fracture injury in the adult skeleton.